2014
DOI: 10.1007/s10943-014-9884-5
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Terminal Values and Religious Experience of God’s Presence and God’s Absence in the Lives of University Students with Various Levels of Empathy

Abstract: The aims of the research I embarked on were: (a) to show the preference of terminal values in personal and in social character, as well to determine the level of religious experience—God’s presence and God’s absence, in groups of young people characterized by a high and low level of empathy and (b) to show the relation between terminal values in personal and in social character and religious experience: God’s presence and God’s absence, in groups of young people with a high and low level of empathy. In the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…This suggests that, in the present case, instrumental values, which define students' standards of behavior, more strongly imply experiences of God's presence than experiences of God's absence, in the lives of both students of pedagogy and students of philosophy. In this regard, our analysis of the issue confirms the findings of certain other studies, which had indicated that instrumental values would contribute more to the occurrence of religious experiences of God's presence than to those of God's absence [5,46].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This suggests that, in the present case, instrumental values, which define students' standards of behavior, more strongly imply experiences of God's presence than experiences of God's absence, in the lives of both students of pedagogy and students of philosophy. In this regard, our analysis of the issue confirms the findings of certain other studies, which had indicated that instrumental values would contribute more to the occurrence of religious experiences of God's presence than to those of God's absence [5,46].…”
Section: Discussionsupporting
confidence: 89%
“…Studies conducted by means of the same Rokeach Value Survey amongst university students belonging to the Roman-Catholic church show that, from among the various possible terminal values, "a sense of accomplishment" is associated with the occurrence of religious experiences of God's presence in their lives, while a high level of empathy and "equality" contribute most to the occurrence of experiences of God's absence. Conversely, in the group of students with a low level of empathy, "social recognition" contributes most to the occurrence of religious experiences of God's presence, while "salvation" does so where experiences of God's absence are concerned [5]. Out of the various possible instrumental values, "helpfulness" contributes most to the occurrence of religious experiences of God's presence in the lives both of students of theology and of students of physics [46], and in the group of young university students with a high level of experience of God's presence terminal values seem to stand in a stronger relation to sensitivity of conscience than instrumental ones [47].…”
Section: The Research Problemmentioning
confidence: 95%
See 2 more Smart Citations
“…Although religious beliefs can at times impede the coping process, they also enable people to understand and deal with stressful situations. In addition, religious practices may foster more effective ways of dealing with stressful situations and conditions [1,26].…”
Section: Religiousness and Copingmentioning
confidence: 99%